Jakość czynnikiem determinującym rozwój eksportu na przykładzie branży spożywczej województwa podkarpackiego - Gil, Katarzyna; Szara, Katarzyna (Quality as the Factor Determining Export Development on the Example of Food Business in Podkarpackie Voivodship, 2005)
Keeping up with the sphere of the quality, being an important benefit in competition between firms, has often become the major determinant of the enterprises' activities. On account of a specific, demanding foreign market, it makes it necessary for firms to conform their production and assortment of products to distinct norms, regulations and customs at the area of production and trade in food and agricultural products and especially to meet specific clients' demands. For this reason many firms in the food and agricultural industry have taken action on the development of quality. As a consequence they achieve better financial and export results.Firms that are interested in improving the quality of their products have gained a competitive advantage over firms which act on interior market and acknowledgement on international market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 231-236